Postoperative Opioid Consumption in Opioid-Naïve Patients Undergoing Hallux Valgus Correction. (November 2019) - Rogero, Ryan; Fuchs, Daniel; Nicholson, Kristen; Shakked, Rachel J.; Winters, Brian S.; Pedowitz, David I.; Raikin, Steven M.; Daniel, Joseph N.
Background: Postoperative pain management following orthopedic surgeries can be challenging, and the opioid epidemic has made it essential to better individualize opioid prescriptions by patient and procedure. The purpose of this subgroup analysis of a prospective study was to investigate immediate postoperative opioid pill consumption and prolonged use in patients undergoing operative correction of hallux valgus (HV). Methods: Patients undergoing outpatient HV correction procedures with 5 fellowship-trained foot and ankle surgeons over a 1-year period were included. Patients were excluded if they were being prescribed chronic opioid analgesics for an underlying condition prior to the date of initial injury or if they underwent concomitant nonforefoot procedures. At the patient's first postoperative visit, opioid pills were counted, and these were standardized to the equivalent number of 5-mg oxycodone pills. Linear regression analysis was performed to determine if any of the procedure categories or patient factors were independently associated with postoperative opioid consumption. Prolonged use of opioids 90 to 180 days after the procedure was also examined using our state's online Prescription Drug Monitoring Program (PDMP). One-hundred thirty-seven patients (86% female) were included. Thirty-six patients (26%) underwent primary chevron osteotomies, 78 (57%) underwent primary proximal osteotomies (Ludloff, scarf), 10 (7%) underwent soft tissue–only procedures with or without a first proximal phalanx osteotomy (modified McBride, Akin), and 13 (9%) underwent first metatarsophalangeal arthrodeses. Results: Overall, patients consumed a median of 27 pills. There was no significant difference in postoperative opioid intake between the 4 procedures, including when subdivided into those with and without lesser toe procedures. Higher preoperative visual analog scale pain levels ( P = .028) and younger patient age ( P = .042) were associated with higher opioid pill consumption. A total of 1.5% of patients demonstrated prolonged opioid use. Conclusion: Our study demonstrated a lack of difference between HV procedures in terms of postoperative opioid consumption and an overall low rate of prolonged use in opioid-naïve patients. Level of Evidence: Level III, comparative study.